2016
DOI: 10.7883/yoken.jjid.2015.098
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Induction of Carbapenem-Resistance in an <i>Aeromonas dhakensis</i> Blood Isolate

Abstract: SUMMARY: Meropenem-susceptible and -resistant Aeromonas dhakensis isolates from blood cultures of a fatal case of septicemia were analyzed. The two isolates were homologous and gene expression of metallo-b-lactamase in the resistant strain was upregulated. Physicians should be aware of the possibility of the induction of carbapenem-resistance, following the use of carbapenems in the treatment of Aeromonas infection.In an earlier study, conducted at a hospital in Japan, we observed that Aeromonas septicemia occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In this study, the susceptible rate of Aeromonas to aminoglycosides and quinolones was > 90%, which is similar to the results of other research results [ 10 , 33 ]. In conformance to other studies, it is worth noting that resistance induction was also found during the treatment period in five cases [ 30 , 34 ]. Four patients developed quinolones resistance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the susceptible rate of Aeromonas to aminoglycosides and quinolones was > 90%, which is similar to the results of other research results [ 10 , 33 ]. In conformance to other studies, it is worth noting that resistance induction was also found during the treatment period in five cases [ 30 , 34 ]. Four patients developed quinolones resistance.…”
Section: Discussionsupporting
confidence: 90%
“…Carbapenem antibiotics are one of the most important empiric therapy for patients with hematological diseases as they exhibit a broad spectrum activity against gram-negative bacilli [ 29 ]. Unfortunately, after using carbapenems for a short time, carbapenem resistance emerges, including Aeromonas [ 30 ]. However, Aeromonas can exhibit rare phenotypes such as carbapenem resistance and cephalosporin susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previously reported cases (Table 2), most were out-of-hospital infections, the disease progressed rapidly, the 14-day mortality rate was high, and the cause of death was mostly bacteremia or systemic infection. These reported cases were all misjudged in the early diagnostic process based on routine biochemical tests and were eventually confirmed by etiological sequencing (6,14,16,18). Pulmonary infection caused by Aeromonas dhakensis has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the production of carbapenem cannot be easily detected in traditional drug sensitivity tests unless a large number of inoculants or additional tests are used. It has been reported that when carbapenem antibiotics were used to treat Aeromonas aeruginosa, A. aeruginosa resistant to carbapenem antibiotics appeared [16]. For severe Candida daca infection, it is suggested that a large number of inoculations and/or additional drug sensitivity tests should be performed prior to carbapenem treatment.…”
Section: Discussionmentioning
confidence: 99%